2014
DOI: 10.1039/c4ay01035c
|View full text |Cite
|
Sign up to set email alerts
|

Development of ssDNA aptamers for the capture and detection of Salmonella typhimurium

Abstract: There is a global need for methods allowing rapid detection of pathogens in food samples, particularly for methods amenable for use in biosensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…by exploiting the surface plasmon resonance features of GNPs. These methods either employ GNPs bound to thiolated DNA or to aptamers for sensitive and selective detection of this deadly pathogen . A new multiplex method for simultaneous detection of three pathogenic bacteria ( S. typhimurium , S. aureus , and Vibrio parahaemolyticus ) has also been demonstrated using aptamer‐conjugated luminescent upconversion nanoparticles .…”
Section: Nanobiosensors For Foodborne Microbial Pathogensmentioning
confidence: 99%
“…by exploiting the surface plasmon resonance features of GNPs. These methods either employ GNPs bound to thiolated DNA or to aptamers for sensitive and selective detection of this deadly pathogen . A new multiplex method for simultaneous detection of three pathogenic bacteria ( S. typhimurium , S. aureus , and Vibrio parahaemolyticus ) has also been demonstrated using aptamer‐conjugated luminescent upconversion nanoparticles .…”
Section: Nanobiosensors For Foodborne Microbial Pathogensmentioning
confidence: 99%
“…With this aptamer, the detection range of 50-10 6 cfu ̸mL and LOD of 5 cfu ̸mL were obtained (Duan et al 2013c). These approaches could be employed to develop an easy, rapid, and sensitive methodology for other closely related pathogen detection in food(s) as only aptamerAuNPs based colorimetric method can detect 10 6 cfu/mL (Moon et al 2014).…”
Section: Salmonella Speciesmentioning
confidence: 99%
“…2) where bound sequences are perfectly separated from unbound ones. Moon and others reported that the use of cell sorting followed by FAM-labeling of aptamer candidates improved the affinity up to a Kd of 3.49 ± 1.43 nM (Moon et al 2014).…”
mentioning
confidence: 99%
“…SELEX-generated aptamers are easier, cheaper, more stable, less immunogenic, allow better synthesis, and exhibit higher productivity than antibodies (Lakhin et al, 2013;Robati et al, 2018;Wu et al, 2012a). Recently, several aptamers have been generated against various targets, such as toxin (Mondal et al, 2018), protein (Hu et al, 2014), antibiotics (He et al, 2013;Song et al, 2011), and whole-cell pathogens (Bayrac¸et al, 2017;Duan et al, 2013aDuan et al, , 2013bDuan et al, , 2016Moon et al, 2014;Suh and Jaykus, 2013;Tianjun et al, 2016;Wu et al, 2012aWu et al, , 2012bYuan et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%